Effects of nerolidol on serum cytokines in acute myocardial infarction: insights into the asprosin, spexin, and DARS2 antibodies in the brain cortex - Erdogan, Mehmet Mustafa; Erdogan, Esra; Kocaman, Nevin; Telo, Selda; Bicen, Hakan; Erdogdu, Hamza; Karakuzulu, Fatma Tuba (Springer, 2025)
BackgroundOxidative stress and inflammation are pivotal in pathogenesis of brain ischemia-reperfusion (I/R) injury. This study evaluated neuroprotective effects of nerolidol (NRD) on asprosin (ASP), spexin (SPX), and DARS2 expressions in myocardial infarction (MI) induced cerebral I/R injury, and systemic inflammatory responses by measuring serum cytokine levels.Methods and resultsTwenty-eight Wistar rats were divided into: Control, MI (200 mg/kg isoproterenol), NRD (100 mg/kg/day), and MI + NRD groups. After 14 days, brain cortex tissues were analyzed histopathologically and immunohistochemically, while serum TAS, TOS, and cytokines were measured via ELISA. Histopathological examination revealed severe cortical damage in MI rats, which was significantly attenuated by NRD treatment. Immunohistochemistry showed marked upregulation of ASP, SPX, and DARS2 in the MI group, with NRD normalizing SPX/DARS2 and partially reducing ASP. Serum analysis revealed comprehensive therapeutic effects of NRD, effectively counteracting the metabolic and inflammatory disturbances caused by MI. The treatment completely restored depleted Metrnl levels to normal values, demonstrating its metabolic regulatory capacity. NRD also showed potent anti-inflammatory action, significantly lowering elevated levels of key pro-inflammatory cytokines while maintaining a balanced immune response. Furthermore, it effectively corrected the oxidative imbalance characteristic of I/R injury, normalizing both oxidant and antioxidant markers to near-control levels. NRD effectively reduces cerebral I/R injury after MI by combining antioxidant, anti-inflammatory, and metabolic regulatory actions. It normalizes Metrnl, cytokines, and oxidative stress markers while modulating ASP/SPX/DARS2 pathways, suggesting their role in both injury and recovery.ConclusionsThese findings highlight the potential of NRD in preventing post-MI brain damage and the need for further research on optimal dosing and mechanistic pathways.
Keywords: Myocardial infarction; Nerolidol; Asprosin; Spexin; DARS2